Wykorzystanie analizy SWOT do podnoszenia konkurencyjności komunikacji marketingowej biur podróży (na przykładzie biur podróży Dolnego Śląska i Śląska Opolskiego) - Przeorek-Smyka, Renata (Application of SWOT analysis for upgrading competitiveness of travel agencies' marketing communication (based on the example of travel agencies in Lower Silesia and Opole Region), 2005)
The article presents practical application of SWOT strategic analysis method for the diagnosis of travel agencies’ marketing communication. The identification and assessment of conducted promotional activities were carried out and both opportunities and threats of their competitiveness were defined. Many factors were analyzed and presented in the cross-section of spheres and areas. Exemplary activities, which upgrade the level of travel agencies’ promotional competitiveness, were also pointed to.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 139-151